Determination of (E) & (Z)-Guggulsterones in Guggul Formulations by High Performance Liquid Chromatography - L. Gottumukkala, Aditya; Ramakrishna, Tummala; Kanna Babu, Sukala; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2016)
A reversed phase high performance liquid chromatography was developed to determine (E) and (Z)-Guggulsterones quantitatively in different guggul formulations. HPLC analysis was performed on a C18 column using 0.1% (v/v) phosphoric acid in water and acetonitrile (45 : 55) as mobile phase with detection at 241 nm. Seven guggul formulations available in the market were analyzed and the quantities of guggulsterones have been found to vary between 0.0022 and 1.2851 mg/capsule. Further, the claimed quantity of guggul on the label did not corroborate with the content of guggulsterones.